Pengaruh Penerapan Pembelajaran Steam Terhadap Kemampuan Memecahkan Masalah Anak Usia Dini - Della Ulia Nendra; Sudarti; Yuniarti Yuniarti (Jurnal Kajian Anak)
Early childhood skills, about problem-solving skills must be fostered because children are essentially individuals who have a sense of interest and curiosity in everything around them, through problem-solving skills will improve children's cognitive. This study aims to determine the conditions before and after the implementation of STEAM learning on early childhood problem-solving skills and to see whether there is an effect of the implementation of this learning. The research method uses a quantitative approach using a one group pre-test-post-test design for one group. There are 17 young children in one class, aged 5-6 years, who are the subjects of the study. The daily implementation learning plan based on STEAM is the tool used. as well as observation sheets, using descriptive statistical data analysis techniques to obtain the average value of children's problem-solving abilities. The results of the study obtained pre-test data from several samples that were not yet able to contribute to problem solving with an average value of 12.35 and post-test results of 26.82 and an N-Gain score of 0.74 which means that children's problem-solving abilities increase with a high category, the conclusion of this study is that the STEAM learning approach is effective in developing children's problem-solving abilities.